Barcode Document Tracking System - Sharifah Saon; Abd Kadir Mahamad; Soon Jian Cheng; Shingo Yamaguchi, (Vol. 1 No. 1 (2019): Internet of Things: Tracking & Monitoring, 2022)
In the era of bombastic technology, our world is occupied with electronic devices. Most of the manual system has been replaced by electronic systems. This can reduce the usage of time, cost and increase the efficiency of the system. Barcode technology is one of the automatic identification and data collection (AIDC) technology that introduce to reduce human error, and reduce time and labor by replacing manual method of data entry and data collection. Barcode technology is allowed to collect real time data with more accurate and faster. Barcode technology consist of the barcode and barcode reader. The combination of barcode technology with computer, database and some of the application software can increase the performance, efficiency and the productivity [1].